Papain Gel as a Deproteinizing Agent for Tooth Enamel - Masiel Monserrat Quintana Sánchez (Mexican Journal of Medical Research ICSA, 2025)
Papain gel has been shown to be an effective deproteinizing agent for tooth enamel in several studies. Papain, a proteolytic enzyme derived from papaya, has the ability to break down proteins and remove organic substances adhering to the surface of the enamel. Its application prior to enamel etching has demonstrated significant benefits, such as removing organic residues and improving the adhesion of dental materials. In addition, papain has been shown to be safe and biocompatible in its dental use. Its mechanism of action is based on its ability to break protein bonds, allowing a deep and effective cleaning of the enamel without compromising its structure. Therefore, this study aims to highlight the importance of papain as an effective and safe alternative in dental treatment, emphasizing its ability to improve the adhesion of dental materials and its specific mechanism of action in the removal of organic residues from tooth enamel.